2021
DOI: 10.1155/2021/9914650
|View full text |Cite
|
Sign up to set email alerts
|

GIS-Based Soft Computing Models for Landslide Susceptibility Mapping: A Case Study of Pithoragarh District, Uttarakhand State, India

Abstract: The main objective of the study was to investigate performance of three soft computing models: Naïve Bayes (NB), Multilayer Perceptron (MLP) neural network classifier, and Alternating Decision Tree (ADT) in landslide susceptibility mapping of Pithoragarh District of Uttarakhand State, India. For this purpose, data of 91 past landslide locations and ten landslide influencing factors, namely, slope degree, curvature, aspect, land cover, slope forming materials (SFM), elevation, distance to rivers, geomorphology,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

6
4

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 93 publications
0
8
0
Order By: Relevance
“…The results show that the random subspace-based extra tree (RSS-ET) model outperforms the random subspace-based (RSS-REPT) and reduced error pruning tree (REPT) models regardless of the performance index is used. Moreover, the prediction accuracy of the random subspace-based extra tree (RSS-ET) model (R 2 = 0.968) developed in this research is higher than the prediction accuracy of the soft computing models currently reported in the literature [49,[104][105][106][107].…”
Section: Comparison Of Developed Modelsmentioning
confidence: 56%
“…The results show that the random subspace-based extra tree (RSS-ET) model outperforms the random subspace-based (RSS-REPT) and reduced error pruning tree (REPT) models regardless of the performance index is used. Moreover, the prediction accuracy of the random subspace-based extra tree (RSS-ET) model (R 2 = 0.968) developed in this research is higher than the prediction accuracy of the soft computing models currently reported in the literature [49,[104][105][106][107].…”
Section: Comparison Of Developed Modelsmentioning
confidence: 56%
“…The paradigm shift in regression models using machine learning significantly contributes to solving engineering problems [ 67 , 68 , 69 , 70 , 71 ]. The current study investigated the effect of changing dosages of NGPs on the mechanical characteristics of concrete.…”
Section: Discussionmentioning
confidence: 99%
“…With the advancement in artificial intelligence (AI), wide variety of civil engineering problems are solved using AI [38][39][40][41][42][43][44][45]. AI models shall be developed that can product the mechanical and durability properties of rubberized concrete.…”
Section: Discussionmentioning
confidence: 99%